Improvement of crawl stroke for the swimming humanoid robot to establish an experimental platform for swimming research - Nakashima, M.; Tsunoda, Y. (Procedia Engineering, 2015)
The objective of this study was to improve the stability of crawl swimming for the swimming humanoid robot. The swimming humanoid robot had 24 servo motors for the whole body and could perform basic human swimming motion. This robot can swim freely by the crawl stroke. However, the robot sometimes changed the propulsive direction while free swimming. The change in the propulsive direction was caused by instability of body rolling. Therefore, swimming motion which could change propulsive direction and roll angle amplitude was examined by simulation. Effectiveness of the devised motion was confirmed by a free-swimming experiment.